Inside Out: A Scoping Review on the Physical Education Teacher’s Personality - Schnitzius, Melina; Kirch, Alina; Mess, Filip; Spengler, Sarah (Frontiers in Psychology, 2019)
The teacher’s personality in general plays an important role in the educational process. It is often examined in relation to outcome factors on the teacher or student side, e.g. teaching effectiveness or student motivation. Physical education (PE) with its peculiarities and allocated educational mandate particularly demands the personality of the PE teacher. Research considering this group of teachers is sparse, diverse and hard to capture due to different personality understandings. Our review therefore aims at identifying and analyzing underlying personality understandings, research questions and results of studies considering the personality of the PE teacher. We conducted a scoping review. After the screening and additional analyses process, 23 studies were included. Included references had to be empirical, published in German or English and explicitly examine the PE teacher’s personality as variable or mention it as outcome factor in school context. All studies are cross-sectional, 22 studies quantitative, one qualitative. Regarding personality understandings, 12 studies follow a trait psychological, six studies a vocational, one study an interpersonal personality understanding. Four studies’ personality understanding is not concretely determinable. Considering research questions, three studies aim at identifying the PE teacher’s personality in general and do e.g. not find considerable differences between the PE teacher’s and other teacher’s personality. Nine studies examine the relationship between the PE teacher’s personality and different correlates such as burnout, highlighting e.g. that female PE teachers’ burnout process is less homogeneous than males. Eleven studies examine the PE teacher’s personality from an external view and show e.g. that students of different age groups perceive the PE teacher’s personality differently. Our review offers possible practical implications. By e.g. knowing their personality structure – their inside –, PE teachers can play to their own strengths and make use of their individual personality configuration in order to teach authentically and successfully, i.e. transferring the inside to the outside. Due to partly questionable and fragmentary methodologies of the included studies, results have to be interpreted with caution. More studies considering the PE teacher’s personality following a broad personality understanding are needed to include potentially relevant factors for teaching and by this receive evident insights.